Evaluation, Comparison and Correlation of the Disease Activity and Damage Index among Patients of SLE with Healthy Controls through Echocardiography - Syed Muhammad Kashif; Iftikhar Haider Naqvi; Muhammad Tanveer Alam; Beenish Imam; Muneeba Khan; Darshan Kumar (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To assess and compare echocardiographic findings in SLE patients with healthy controls and their correlation with disease activity and damage index. METHODOLOGY: This cross-sectional study was undertaken in the Department of Medicine, Civil Hospital Karachi, an affiliated hospital of Dow University of Health Sciences (DUHS) Karachi, Pakistan, from January to July 2023. Forty-one patients with SLE and Thirty-nine healthy controls were enrolled, undergoing echocardiographic analysis for cardiovascular complications with the clinical and biochemical profile. Statistical differences among groups were assessed using the Chi-square test for qualitative variables and the independent sample t-test for quantitative variables. The correlation between disease severity and cardiovascular events was determined by Pearson correlation. P ? 0.05 was measured as statistically significant. RESULTS: The most common valvular abnormality was mitral regurgitation (48.7%), then tricuspid regurgitation (21.9%), aortic regurgitation (17.7%), mitral stenosis (2.4%) and mitral valve prolapse (4.8%) in SLE, Left ventricular internal diameter end diastole [p 0.001], Intraventricular septal wall thickness, and end-diastolic left ventricular internal diameter end-systole [p 0.002] were found statistically significant among the groups. Left ventricular posterior wall end-diastole [p < 0.00001] and pulmonary artery systolic pressure [p < 0.00001] were also substantial among groups. Lupus nephritis positively correlated to ejection fraction (r=0.00013, p 0.56). CONCLUSION: Cardiovascular complications are frequently reported in SLE, as assessed by echocardiographic findings. SLE severity is related to echocardiographic changes, and SLE with secondary Antiphospholipid syndrome (APS) significantly affects renal, haematological, and echocardiographic parameters.